The Reality of Green Training from the Employees' Perspective at Al-Jouf Oil Technology Company in Benghazi: A Field Study (Comprehensive Journal of Science, 2025)
This study aimed to evaluate the reality of Green Training at Jowfe Oil Technology Company in Benghazi, Libya. This was achieved by identifying the level of employee perception regarding the concept of Green Training across its three dimensions: Green Knowledge, Green Skills, and Green Motivation. Additionally, the study investigated whether there were statistically significant differences in employee responses attributable to certain personal and occupational variables (Gender, Age, Educational Level, Length of Service).The study adopted a descriptive approach, and data was collected using interviews and a questionnaire, based on relevant previous studies. The study population consisted of all employees at Jowfe Oil Technology Company (850 employees). A simple random sample of 200 employees was selected, with a final response rate of 75.5%. Data was analyzed using the Statistical Package for the Social Sciences (SPSS).The results indicated that the overall level of Green Training in the company, as perceived by employees, was High. The Green Knowledge dimension ranked first, followed by Green Motivation in second place, while the Green Skills dimension came in last. This suggests that the company needs to focus its efforts on developing the practical capabilities of its employees.The study also proved the existence of statistically significant differences in perception attributable to the Age variable, with the age group (35 to 45 years) being the most perceptive. Conversely, no significant differences were found based on the variables of Gender, Educational Level, or Length of Service, indicating that training programs are implemented uniformly.The study concluded with a set of recommendations, including: the necessity of developing training programs to enhance the Green Skills dimension, leveraging the most perceptive age group as leaders for environmental work, and reinforcing motivation mechanisms to ensure the effective participation of all employees.
Keywords: Green Training, Jowfe Oil Technology Company, Benghazi-Libya